Cancelamento de cirurgias eletivas: dos motivos à compreensão do itinerário Agendamento-Centro Cirúrgico - Santos, Gisele Aparecida Alves Corral dos [UNESP] (2015)
Objectives. (a) To characterize the cancellations of elective surgeries for clinical and non-clinical reasons, in 2013, as well as check for influence of seasonality in the period from 2010 to 2013; (b) to understand the experience of the involved actors in canceled elective surgical itinerary Surgical Scheduling - Ambulatory - Inpatient Units - Sterilized Material Center (CME) - Surgical Center (CC); (c) to elaborate theoretical model representing this experience. Methods. Mixed research, being the first a quantitative design, comprising secondary data from a Public Hospital of São Paulo database, about the surgical cancellations occurred in 2013, to achieve the objective (a). Descriptive statistics was applied, while the Poisson regression model adjusted to identify monthly differences was applied only to analyze seasonal trends concerning reasons for cancelations. The second method applied was qualitative, to meet the objectives (b) and (c). Semi-structured and individual interviews were conducted with the actors of the units which comprised the surgical itinerary, totaling 21 professionals: three doctors, 11 nurses, five technician nurses and two administrative officers. The interviews were recorded, transcribed and analyzed according to the steps of the Grounded Theory. Results. From 8.443 (100%) scheduled as elective surgeries, 7 870 (93.21%) were performed, and 573 (6.79%) canceled. Considering these 573 (100%), 48.33% were for medical reasons and 46.40% for non-clinical. Among the non-clinical reasons of surgical cancellation, predominated the ones referring to medical reasons, categorized as requested by the surgeon / change in conduct (17.93%), followed by patient not hospitalized (8.96%). Cancellations reached peaks at 7:00 AM and at 01:30 PM, due to lack of the patient's clinical conditions, and request of the Surgeon / change in conduct. Children and the elderly totaled 61.86% of ...